Analisis kewenangan dan bentuk pengawasan inspektorat oleh Aparat Pengawasan Intern Pemerintah (APIP) di Inspektorat Provinsi Sulawesi Utara - Lii, Rosdina Arini; Wokas, Heince R. N.; Suwetja, I Gede (Riset Akuntansi dan Portofolio Investasi, 2025)
The Internal Government Supervisory Apparatus (APIP) functions as an internal audit body within the Regional Inspectorate to ensure accountability and efficiency in local governance. This study aims to analyze the authority and forms of supervision conducted by the Provincial Inspectorate of North Sulawesi. Using a qualitative descriptive approach, data were collected through structured interviews with three key informants: an Assistant Inspector, a Junior Auditor, and a Regional Government Affairs Supervisory Officer. The results indicate that APIP carries out three main supervisory activities: audit, review, and evaluation, which are essential for preventing irregularities and improving performance. Despite these contributions, APIP faces challenges, including limited access to data, lack of transparency from auditees, and potential ethical issues during the process. Strengthening APIP’s authority and enhancing coordination are critical to improving governance and reducing risks of fraud. The dual role of APIP as an assurance provider and consultant further reinforces its strategic contribution to good governance in local government administration.